Textual Criticism: An Exegetical Exploration of the Phrase ‘(τῇ) μιᾷ (τῶν) σαββάτων’: The Controversy on the Sunday Resurrection - Muner Daliman; Hana Supati; K.H Sugiyarto (Pharos Journal of Theology)
The phrase (tē) mia (tōn) sabbatōn, translating to "the first of the Sabbaths," has been a focal point in discussions concerning the resurrection of Jesus Christ, particularly regarding the day on which it is believed to have occurred. This controversy is rooted in textual criticism, which examines variations in biblical manuscripts to determine the most accurate interpretation of Scripture. The phrase “(te) mia (ton) sabbabton” translates to "the first of the Sabbath" and has been a focal point in discussions surrounding the resurrection of Jesus Christ, particularly regarding the day it is believed to have occurred. This controversy is rooted in textual criticism, which examines variations in biblical manuscripts to ascertain the most accurate interpretations of scripture. From re-analyzing the related of and the Greek phrase ‘(tē) mia (tōn) sabbatōn’, it can be concluded that the crucifixion of Jesus was on Wednesday, 24 March and the resurrection was on Saturday (Sabbath), 27, March of 34 CE.